PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PEMALSUAN TANDA NOMOR KENDARAAN BERMOTOR DI KOTA PEKANBARU - M REZKY RAMADHAN; Dessy Artina; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Legal certainty without being based on the joints of justice will causedissatisfaction and invite many reactions. The law functions as a social control(social control) can be interpreted, namely as a process whether planned or not,which is educational, inviting or even forcing citizens to comply with theprevailing system of rules and values. At this time in the city of Pekanbaru, therewere many perpetrators of the Counterfeiting of Motorized Vehicle Number Signs(TNKB). According to Article 263, namely: